Utilization of aspen and poplars (genus Populus) - Kärkkäinen, Matti (Silva Fennica, 1981)
The aim of this study was to establish from the literature the purposes and for which aspen (Populus tremula L.) and related poplar species are used and can be used.  According to the literature, numerous species can be utilized in the industry with success instead of light softwood species in addition to them. The main emphasis is in the growing of large-sized timber, and there is no clear trend to changing to the short-rotation forestry of poplar. However, the utilization of the good sprouting properties of Populus species will probably increase as this regeneration method is cheap.Populus